EVALUATION OF ANTIBACTERIAL PROPERTIES OF FRUIT PEEL EXTRACTS OF CITRUS KARNA AGAINST HUMAN PATHOGENS - SIKANDER DAR,; REENA S LAWRENCE, (International Journal of Pharma and Bio Sciences, 2015)
The antibacterial activity of Citrus karna fruit peel extracts was evaluated on bacteria strains like Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus subtilis. Hexane, chloroform and methanol were used for extraction and the antibacterial activity was performed by agar well diffusion method. The results were compared with ampicillin, a commercial antibacterial agent. Methanolic extract shows the highest antibacterial activity against all the four bacterial strains, whereas hexane extract shows lowest antibacterial activity. Among the tested bacterial isolates P. aeruginosa was the most inhibited majorly with the methanol extract. The methanolic extract shows lowest (14mm) zone of inhibition against B. subtilis. The chloroform extract displayed inhibitory zones of between 12-15mm while the hexane extract exhibited inhibitory affinity between 11-13mm. The MIC of the plant extracts on the susceptible bacterial isolates was between 37-333µg/ml. Present study concludes that fruit peels of Citrus karna have a broad spectrum antibacterial activity against human pathogens.